EFFECT OF WARP YARN TENSION ON CRIMP% IN WOVEN FABRIC - Farhana Afroz; Ayesha Siddika (European Scientific Journal, ESJ, 2014)
Yarn tension is the most important factor that affects weaving performance and fabric property. Experimental studies were conducted by woven fabrics which are produced by rapier loom (Dobby shedding). The study shows that yarn crimp in woven fabric is affected by yarn tension. Crimp% was calculated by dividing the uncrimped length of yarn by crimped length of yarn. It was observed that crimp% of warp and weft yarn in woven fabric is affected by warp and weft yarn tension.